Efektivitas Ekstrak Biji Kapas (Gossypium hirsutum L.) terhadap Jumlah dan Viabilitas Embrio Mencit (Mus musculus L.) - Nofri Zayani; Iman Supriatna; Mohamad Agus Setiadi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The cottonseed (Gossypium hirsutum L.) contained gossypol as antifertility agent. The effect of cottonseed extract treatment could be decrease and impaired follicles development were accompanied by oocytesdamage. Damage of oocytes resulted reduction of number and viability of embryos. The objective of this study was to evaluate the effectiveness of cottonseed extract (Gossypium hirsutum L.) on the number and viability ofmice embryo (Mus musculus L.). Doses of the cottonseed extract were used consists of 0 (control), 1.5; 2.1; and 2.7 g/kg of body weight (BW) for 24 days via the oral route. This research used 24 animals healthy of femaleDDY mice 14-15 weeks old and 30-35 g BW. Embryos were collected at day 4 of pregnancy by flushing the utery cornua. The collected embryos were cultured in vitro for 48 hours in modified phosphate buffered saline (PBS) supplemented with 10% fetal bovine serum (FBS) culture medium according to the stage of its development to observe the viability of embryos. The result showed that the cottonseed extract with doses 1.5; 2.1; and 2.7 g/kg of body weight (BW) made the number of embryos which collected in D4 of pregnancy significantly lowerthan control (P<0.05). Data from embryos culture in vitro for 48 hours decreased embryos number (P<0.05) that developed in to the expanded and hatched blastocysts. At 2.7 g/kg BW, embryos only can develop to theblastocysts stage. Retardation (4-8 cells) and degeneration embryos did not develop in culture